Employing parent-teacher collaboration to enhance intrinsic motivation, creating a positive classroom climate and improved academic achievements In Arab School in Israel - Abu-Asbeh, Khaled (Advances in Social Sciences Research Journal, 2017)
This study investigated ways in which intrinsic motivation can be enhanced to improve learning achievements and the correlation between motivation and classroom climate in an Arab public high school in Israel.187 school students in Grade 11 participated in the study which involved two main stages: (a) the investigation stage: examining the classroom climate, intrinsic motivation, sense of affiliation to the school, sense of wellbeing, and academic achievements in core disciplines, in addition to other relevant variables. (b) the implementation stage: this stage was performed with a set of workshops for teachers and parents over a period of six months, aimed at helping parents and teachers to improve the students’ intrinsic motivation for learning. After the workshops, a questionnaire was administered for a second time to the students who had taken part in the investigation stage. Findings from the questionnaires revealed a positive correlation between students’ level of achievements and the level of their intrinsic motivation, sense of belonging to the school and sense of wellbeing, and their perception of the classroom climate. All these components were found to have higher values among female students than among male students. It was concluded that the use of principles encouraging intrinsic motivation improved the level of the different components. Moreover, it was found that the use of these principles that encouraged intrinsic motivation only improved academic achievements among the male students, while among the female students the use of the same principles improved all the components.